Integrated Proteomic and Transcriptomic Analysis Reveals Long Noncoding RNA HOX Transcript Antisense Intergenic RNA (HOTAIR) Promotes Hepatocellular Carcinoma Cell Proliferation by Regulating Opioid Growth Factor Receptor (OGFr) - Wu, Ying; Xiong, Qian; Li, Siting; Yang, Xue; Ge, Feng (Molecular & cellular proteomics, 2018)
Long noncoding RNA HOX transcript antisense RNA (HOTAIR) is involved in human tumorigenesis and is dysregulated in hepatocellular carcinoma (HCC). However, the molecular mechanisms underlying HOTAIR functions in HCC are largely unknown. Here, we employed an integrated transcriptomic and quantitative proteomic analysis to systematically explore the regulatory role of HOTAIR in HCC. A total of 673 transcripts and 293 proteins were found to be dysregulated after HOTAIR inhibition. Bioinformatics studies indicated that differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) are involved in many biological processes, especially cancer-related signaling pathways. A set of DEGs and DEPs were validated by quantitative RT-PCR, Western blot and parallel reaction monitoring (PRM) analysis, respectively. Further functional studies of the opioid growth factor receptor (OGFr), a negative biological regulator of cell proliferation in HCC, revealed that HOTAIR exerts its effects on cell proliferation, at least in part, through the regulation of OGFr expression. By correlating the omics data with functional studies, the current results provide novel insights into the functional mechanisms of HOTAIR in HCC cells.